Macrophage-Based Therapies for Atherosclerosis Management. (29th January 2020) - Peng, Renyi; Ji, Hao; Jin, Libo; Lin, Sue; Huang, Yijiang; Xu, Ke; Yang, Qinsi; Sun, Da; Wu, Wei
Abstract : Atherosclerosis (AS), a typical chronic inflammatory vascular disease, is the main pathological basis of ischemic cardio/cerebrovascular disease (CVD). Long-term administration was characterized with low efficacy and serious side effects, while the macrophages with attractive intrinsic homing target have great potential in the efficient and safe management of AS. In this review, we focused on the systematical summary of the macrophage-based therapies in AS management, including macrophage autophagy, polarization, targeted delivery, microenvironment-triggered drug release, and macrophage- or macrophage membrane-based drug carrier. In conclusion, macrophage-based therapies have great promise to effectively manage AS in future research and clinic translation.